Stability and Oligomerization of Mutated SMN Protein Determine Clinical Severity of Spinal Muscular Atrophy - Niba, Emma Tabe Eko; Nishio, Hisahide; Wijaya, Yogik Onky Silvana; Ar Rochmah, Mawaddah; Takarada, Toru; Takeuchi, Atsuko; Kimizu, Tomokazu; Okamoto, Kentaro; Saito, Toshio; Awano, Hiroyuki; Takeshima, Yasuhiro; Shinohara, Masakazu (MDPI, 2022)
Spinal muscular atrophy (SMA) is a common autosomal recessive neuromuscular disease characterized by defects of lower motor neurons. Approximately 95 of SMA patients are homozygous for survival motor neuron 1 (SMN1) gene deletion, while ~5 carry an intragenic SMN1 mutation. Here, we investigated the stability and oligomerization ability of mutated SMN1 pro-teins. Plasmids containing wild-and mutant-type SMN1 cDNA were constructed and transfected into HeLa cells. Reverse transcription-polymerase chain reaction (RT-PCR) demonstrated similar abundances of transcripts from the plasmids containing SMN cDNA, but Western blotting showed different expression levels of mutated SMN1 proteins, reflecting the degree of their instability. A mutated SMN1 protein with T274YfsX32 exhibited a much lower expression level than other mutated SMN1 proteins with E134K, Y276H, or Y277C. In immunoprecipitation analysis, the mutated SMN1 protein with T274YfsX32 did not bind to endogenous SMN1 protein in HeLa cells, suggesting that this mutation completely blocks the oligomerization with full-length SMN2 protein in the patient. The patient with T274YfsX32 showed a much more severe phenotype than the other patients with different mutations. In conclusion, the stability and oligomerization ability of mutated SMN1 protein may determine the protein stability and may be associated with the clinical severity of SMA caused by intragenic SMN1 mutation. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.